Social Entrepreneurship Mentoring through Business Technology Incubation for Beneficiary Families in West Sumatra: Pendampingan Kewirausahaan Sosial melalui Inkubasi Bisnis Teknologi bagi Keluarga Penerima Manfaat di Sumatera Barat - Berri Brilliant Albar; Ares Albirru Amsal (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
The Social Entrepreneurship Assistance Program, implemented through a collaborative partnership between the Ministry of Social Affairs of the Republic of Indonesia and the Technology Business Incubator of Universitas Andalas, was designed to strengthen the economic independence of vulnerable households through entrepreneurship development. The program involved 350 Beneficiary Families (Keluarga Penerima Manfaat, KPM) across Padang City (150 participants), Pariaman City (100 participants), and Tanah Datar Regency (100 participants), West Sumatra, Indonesia. According to Statistics Indonesia (BPS), vulnerable communities experience disproportionately high rates of micro-enterprise failure due to inadequate business planning and limited managerial capacity. This community development initiative adopted a Participatory Action Research (PAR) approach integrated with a structured business incubation model. The intervention consisted of regional coordination, participant screening, a Training of Trainers (TOT) program for 20 local mentors, and three months of intensive field mentoring. Capacity-building activities emphasized business model development using the Business Model Canvas (BMC) and SWOT analysis, financial literacy and bookkeeping, and productive asset enhancement through financial assistance of IDR 600,000 for each beneficiary family. In addition, a Virtual Expo platform was established to improve product promotion and expand market access. The program achieved a 100% completion rate in business model development, while 85% of participants consistently adopted daily cash bookkeeping practices. These findings indicate that strategic collaboration between university-based technology business incubators and government institutions can effectively enhance entrepreneurial capacity, reduce micro-enterprise risks, and promote sustainable socio-economic empowerment by transforming vulnerable households into resilient and independent entrepreneurs.